Bioethics in tissue engineering in the Muslim world - Sha'ban, Munirah (Eubios Ethics Institute, 2010)
The multidisciplinary field of tissue-engineering was born as a means to restore or replace diseased tissue with new living tissue that is designed or constructed to meet the needs of each individual patient. Scientific advances in biomaterials, stem cells, growth factors, and biomimetic environments have created opportunities to reconstruct tissues from combinations of engineered scaffolds, cells and biologically active signaling molecules. Accordingly, advanced developments in tissue-engineering have yielded a novel set of engineered tissue implants and treatment approaches. The demand for these tissueengineered products may increase significantly, but, the progress has been slow due to scientific and technical difficulties that subject to a wide variety of philosophical, religious and ethical challenges, and economic viewpoints....